2018
DOI: 10.1021/acs.nanolett.8b03568
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Tumor-Associated Macrophages by Nanoparticle-Based Reactive Oxygen Species Photogeneration

Abstract: Without coordinated strategies to mitigate the immunosuppressive nature of the tumor microenvironment, cancer immunotherapy generally offers limited clinical benefit for established tumors. Tumor-associated macrophages (TAMs) are the critical driver of this immunosuppressive tumor microenvironment, which also promotes tumor metastasis. Here we successfully reprogrammed TAMs to an antitumor M1 phenotype using precision nanoparticle-based reactive oxygen species photogeneration, which demonstrated superior effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
154
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(154 citation statements)
references
References 46 publications
0
154
0
Order By: Relevance
“…[162] They synthesized endosome-escaping and TAM-targeting PEG-PLGA NPs for encapsulation of photosensitizers with NH 4 HCO 3 . Shi et al found that the intracellular photogeneration of ROS was able to regulate the reprogramming of TAMs toward M1 phenotype.…”
Section: Combination Of Immunotherapy and Traditional Managementsmentioning
confidence: 99%
“…[162] They synthesized endosome-escaping and TAM-targeting PEG-PLGA NPs for encapsulation of photosensitizers with NH 4 HCO 3 . Shi et al found that the intracellular photogeneration of ROS was able to regulate the reprogramming of TAMs toward M1 phenotype.…”
Section: Combination Of Immunotherapy and Traditional Managementsmentioning
confidence: 99%
“…Also in 2017, Goldberg and co‐workers developed PLGA nanoparticles decorated with anti‐PD‐1 to target T cells as well as release R848 (resiquimod, a TLR7/8 agonist) and SD‐208 (a transforming growth factor‐β (TGF‐β) receptor inhibitor) to block the immunosuppressive effects of TGF‐β and potentiate an antitumor response . In 2018, Chen and co‐workers leveraged PLGA nanoparticles to deliver reactive oxygen species (ROS)‐generating species to repolarize tumor‐associated macrophages (TAMs) toward an M1 phenotype and subsequently orchestrate CTL recruitment . Finally, several groups have looked to incorporate photothermal agents into PLGA nanoparticles to enable photothermal therapy (PTT).…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…[26] In 2018, Chen and co-workers leveraged PLGA nanoparticles to deliver reactive oxygen species (ROS)-generating species to repolarize tumor-associated macrophages (TAMs) toward an M1 phenotype and subsequently orchestrate CTL recruitment. [27] Finally, several groups have looked to incorporate photothermal agents into PLGA nanoparticles to enable photothermal therapy (PTT). Liu and co-workers showed that PLGA nanoparticles encapsulating indocyanine green (ICG, a PTT agent) and imiquimod (an adjuvant) in combination with free anti-cytotoxic T lymphocyte antigen (CTLA)-4 (a checkpoint inhibitor) led to potent antitumor responses in mice with 4T1 triple negative breast cancer.…”
mentioning
confidence: 99%
“…Most stimuli-responsive NPs rely on hypoxic or acidic dysregulation within tumors. [63] These data emphasize the utility of targeting a biological mechanism of innate immune cells in the primary tumor. [60] There are many approaches that have leveraged pH-regulated degradation in tumors as a means to release a therapeutic, like TNFα.…”
Section: Biomaterials Can Deliver Payload In Response To Unique Featumentioning
confidence: 93%
“…To mimic the APC presentation of cytokines to T cells, Eggermont et al recently utilized a polyisocyanopeptide (PIC) backbone appended with controlled densities and ratios of an antibody that binds to a T cell receptor (cluster of differentiation 3, CD3); these constructs also integrated IL-2 or IFNα to stimulate T cell proliferation ( Figure 3B). [63] Copyright 2018, American Chemical Society. Formulations that included either IL-2 or IFNα demonstrated an ability to induce [53] Copyright 2018, The American Association of Immunologists, Inc. B,C) Artificial APCs that control the presentation of cytokines to T cells and D) incorporate T cell costimulatory factors to generate cytotoxic T cells.…”
Section: Vaccines and Artificial Apcs Program Antigen Presentationmentioning
confidence: 99%